Gut microbiome-immune interactions and their role in rheumatoid arthritis development - Madiyar Nurgaziyev; Argul Issilbayeva; Rakhmetkazhi Bersimbaev; Oralbek Ilderbayev; Elizaveta Vinogradova; Zharkyn Jarmukhanov; Ayaulym Nurgozhina; Shynggys Sergazy; Nuray Kozhabergen; Zhanar Akhmetova; Assel Meiramova; Laura Chulenbayeva; et al. (PeerJ, 2024)
Objective The primary objective is to study the impact of gut microbiota and their interactions with diverse immunological markers on the development of rheumatoid arthritis. Methods This study was performed in Astana, Kazakhstan, and included 77 Kazakh female patients older than 18 years, who met the American College of Rheumatology 2010 classification criteria for rheumatoid arthritis (RA), and 113 healthy controls. The DNA was extracted from fecal samples obtained from all study participants for subsequent sequencing at the 16S rRNA gene V1-V3 locus, facilitating the analysis of the gut microbiome. The Multiplex immunoassay was employed to measure the concentrations of inflammatory cytokines, chemokines, and immunoglobulins in both fecal and plasma samples. Results Our taxonomic analysis revealed significant differences in the composition of the gut microbiota between the healthy control cohort and the cohort with rheumatoid arthritis RA. Alpha diversity was significantly lower in the RA group. Lachnospiraceae were the most abundant taxon and found to be crucial, showing correlations with immunological markers such as IL5. Additionally, Lachnospiraceae and Oscillospiraceae exhibited the most predictable power and distinguished the composition of both study groups. Conclusion Our study identifies key differences in the gut microbiome of RA patients, revealing distinct microbial patterns and specific taxa abundance. We highlight potential biomarkers in immunological and bacterial pathways, offering insights into RA development and indicating possibilities for personalized treatment.